Hospital infections in ICUs and their ralationship withhand hygienization in a unisersity hospital in the Northeast: Epidemiological study (Research, Society and Development, 2023)
Objective: To investigate the epidemiological profile of HAIs in the Intensive Care Unit (ICU) of a Reference Hospital in the Northeast. Methodology: This is a cross-sectional study with a quantitative approach, which aims to observe and obtain reliable data for research with the aim of concluding with reliable data. Result: Among the participants, there was a predominance of males and the age group that includes the elderly – adults. The specialty that had the highest number of patients was the medical clinic, followed by cardiology. The infection with the highest prevalence was laboratory ventilator-associated pneumonia (VAP) (43.0%) among the total number of infections. Attention is also drawn to primary bloodstream infection (IPCSL), with (15.3%) pyogenic IPCSL and 3 (2.3%) contaminating IPCSL, and urinary tract infection (UTI) (13.0%). The most prevalent isolated microorganism was pseudomonas aeruginosa (28.3%), followed by klebsiella pneumoniae (18.3%), acinetobacter baumannii (15.8%). Regarding the rate of adherence to hand hygiene in 2022 with a median of 66.0%. In 2023, between the months of January and July, the median was 62.8%. Conclusion: The number of patients with HAIs is still high. Therefore, it is important to highlight the control and prevention of HAIs following patient safety protocols, considering that these infections are directly linked to the quality of care provided.